Monkeypox Outbreak in Non-Endemic Areas: Will it Cause a New Pandemic? a Letter to Editor - Alavi-Moghaddam, Mostafa (Archives of Academic Emergency Medicine, 2022)
Monkeypox (MP) is a rare endemic infection found in tropical rainforest areas of west or central Africa. The recent world health organization (WHO) reports of confirmed MP cases from non-endemic areas have raised global concern over the risk of a new pandemic. Monkeypox is a misnomer, as the first confirmed case of MP was diagnosed in a monkey in 1958; however, MP virus is a viral zoonosis that belongs to Orthopoxvirus genus of the Poxviridea family and in addition to old and new world monkeys and apes, it can infect rats, mice, squirrels, prairie dogs, and rabbits (1). MP virus can be transmitted through touching blood, body fluids, spots, blisters or scabs of infected animals or infected persons. MP virus is also spread through touching the clothing, bedding, or towels of infected persons. Face to face exposure to infected persons and eating raw or under-cooked meat from infected animals are other sources of infection (2).